2011
DOI: 10.1080/02687038.2011.603898
|View full text |Cite
|
Sign up to set email alerts
|

Lexical diversity for adults with and without aphasia across discourse elicitation tasks

Abstract: Background Differences in lexical diversity (LD) across different discourse elicitation tasks have been found in neurologically intact adults (NIA) (Fergadiotis, Wright, & Capilouto, 2010) but have not been investigated systematically in people with aphasia (PWA). Measuring lexical diversity in PWA may serve as a useful clinical tool for evaluating the impact of word retrieval difficulties at the discourse level. Aims The study aims were (a) to explore the differences between the oral language samples of PWA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 68 publications
4
77
0
2
Order By: Relevance
“…Speakers with aphasia produce discourse that is impaired in terms of syntax [52][53][54][55]. Evidence from retellings of the Cinderella story is a particularly rich source of information about syntactic difficulty for PWA [9,55,56].…”
Section: Discourse Patterns In Aphasiamentioning
confidence: 99%
“…Speakers with aphasia produce discourse that is impaired in terms of syntax [52][53][54][55]. Evidence from retellings of the Cinderella story is a particularly rich source of information about syntactic difficulty for PWA [9,55,56].…”
Section: Discourse Patterns In Aphasiamentioning
confidence: 99%
“…This study used a sample of discourse from each participant elicited by the retelling of the Cinderella story. This particular discourse elicitation task was chosen as it has been demonstrated that during story retell procedures, individuals tend to produce language with significantly higher lexical diversity than during picture description tasks (Fergadiotis & Wright, 2011). This suggests that story retell tasks produce language samples that are more representative of the individual's best semantic abilities than samples elicited by picture description.…”
Section: Data Sourcementioning
confidence: 99%
“…Finally, individuals with syntactic deficits tend to show reduced use of function words, such as auxiliary verbs, articles, and prepositions . With regards to semantic impairment, individuals with semantic access deficits tend to use fewer different types of words (Fergadiotis & Wright, 2011), and may omit words that are important to convey critical information, such as in retelling a story (Ernest-Baron, Brookshire, & Nicholas, 1987), due to reduced capacity to access semantic representations. These individuals may also demonstrate decreased semantic density, using more words than necessary to convey the same amount of information (Bryant et al, 2013).…”
Section: And Thenmentioning
confidence: 99%
“…Covington and McFall (2010) proposed a new measure called the moving-average type-token ratio (MATTR), which is independent of text length. This feature was later applied to aphasic speech in a study by Fergadiotis and Wright (2011), and was found to be one of the most unbiased indicators of lexical diversity in impaired speakers.…”
Section: Vocabulary Richness Featuresmentioning
confidence: 99%